1997
DOI: 10.1046/j.1365-2796.1997.136142000.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individuals with high fat levels and low P∶S ratios, in their diets, for intensive dietary intervention

Abstract: Abstract. Kinlay S, Elliott H, Heller RF (University of Newcastle, Royal Newcastle Hospital, Newcastle, NSW, Australia). Identifying individuals with high fat levels and low P : S ratios, in their diets, for intensive dietary intervention. J Intern Med 1997 ; 241 : 407-14.Objectives. To assess whether simple scores from a dietary questionnaire could identify those with high dietary fat or low P : S ratio intakes, for intensive dietary intervention. Design. Cross-sectional and longitudinal studies. Setting. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Only Kristal et al (1990a,b) found comparable, and reasonably high correlations for both absolute intake as well as percentage energy from fat. The study of Kinlay et al (1997) among youngsters showed acceptable correlations for percentage energy from fat and saturated fat for this age group. The low correlation between the fat score and percentage energy from fat or from saturated fat in the present study, may be explained by the very high correlation between total fat intake and total saturated fat: r 0.95 for adults and 0.67 for adolescents) (as in Gray-Donald et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Only Kristal et al (1990a,b) found comparable, and reasonably high correlations for both absolute intake as well as percentage energy from fat. The study of Kinlay et al (1997) among youngsters showed acceptable correlations for percentage energy from fat and saturated fat for this age group. The low correlation between the fat score and percentage energy from fat or from saturated fat in the present study, may be explained by the very high correlation between total fat intake and total saturated fat: r 0.95 for adults and 0.67 for adolescents) (as in Gray-Donald et al, 1997).…”
Section: Discussionmentioning
confidence: 81%
“…A literature search of publications since 1980 reveals that there have been a number of earlier validation studies of fat intake questionnaires with less than 50 questions (Table 8). The correlations between the results of the short instrument and a reference instrument found in these studies indicate that the Fat list in the present study seems to categorize adult individuals according to absolute total and saturated fat intake as well as or better than other short fat intake questionnaires (Block et al ., 1989; Coates et al ., 1995; Heller et al ., 1981; Pietinen et al ., 1988; Kristal et al ., 1990a,b;Connor et al ., 1992; Van Assema et al ., 1992; Gray‐Donald et al ., 1997; Kinlay et al ., 1997; Retzlaff et al ., 1997; Shannon et al ., 1997; Persson et al ., 1998). We could find only one publication of a validation of a short questionnaire that included the important subpopulation of youngsters (Kinlay et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations